The Fat Leading the Thin: Relative Body Size, Physical Activity Identification, and Behavioral Problems - Andrew C. Pickett; George B. Cunningham (Journal of Applied Sports Management, 2018)
Though sport and physical activity participation are key elements of a healthy lifestyle, anti-fat biases serve as barriers to active living, leaving a large population segment underserved. This stigma also creates thin body standards for people working in sport and physical activity, including instructors. In this study, the authors conducted an experiment to explore how instructor and participant body size interact to influence activity identification and subsequent intentions to be physically active. Results indicate that larger-bodied participants were more identified when working with a larger instructor. For thinner participants, there were no significant differences in identification related to instructor body size. Identification was positively related to future intentions in the activity. Implications for practice are discussed. Subscribe to JASM
Keywords: Stigma; Physical Activity; Body Weight; Instructor; Fat